TRADISI PERKAWINAN DI KENEGERIAN KOPAH KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Mailan Eka Sari; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is proposed to quality a bachelor’s degree in sosiology. With the tittle “Change of Marriage Tradision in Kenegerian Kopah Kecamatan Kuantan Singingi District”. This research aims to know the proses of implementation of marriage tradision in Kenegerian Kopah, to know what elements are experiencing change, and to determine the factors that cause changes in the implementation of marriage in Kenegerian Kopah. This research uses qualitative analysis method, the subject of this research is determined by purposive sampling techniques and data collection techniques using observation, interviews, and documentation. The results of this research indicate that the social changes that occur in Kenegerian Kopah society is in the tradision of marriage. In the past the pratice of marriage was fully practiced by custom. But now more lead to more practical implementation. The proses of implementation of the marriage tradision in Kenegerian Kopah such as, fiance “ma ikek tando” determine the date before the wedding, marriage ceremony “ampokat”, and marriage receprions. Changing elements such as, introduction phase, way find a partner, marriage procedures, marriage receptions, marriage of one tribe. Some of the factors that cause change are, the change of society it self, the level of education, people who are more interest in practical marriage, the influence from outside and mixing culture, contact with other people, preparation before teh wedding.The key word : Change, Tradition, the Marriage